2015
DOI: 10.1002/cbic.201500542
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Understanding the Genetic Information and Biosynthetic Pathways behind Amycolatopsis Antibiotics, with Implications for the Continued Discovery of Novel Drugs

Abstract: Species of Amycolatopsis, well recognized as producers of both vancomycin and rifamycin, are also known for producing other secondary metabolites, with wide usage in medicine and agriculture. The molecular genetics of natural antibiotics produced by this genus have been well studied. Since the rise of antibiotic resistance, finding new drugs to fight infection has become an urgent priority. Progress in understanding the biosynthesis of metabolites greatly helps the rational manipulation of biosynthetic pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 82 publications
0
36
0
Order By: Relevance
“…The genomic studies have revealed that Amycolatopsis have comparatively large genomes *5 Mb (A. halophila YIM93223-10) to 10.86 Mb (A. balhimycina FH 1894), circular chromosomes and contains over 20 secondary metabolic gene clusters. As these bacteria are mostly soil dwellers, they experience a diverse and changing habitat which may benefit from a larger repertoire of genes allowing the organism to acclimatize and adapt to the changing conditions [17]. The occurrence of indigenous plasmids in this genus is also not very common.…”
Section: General Features Of the Genus Amycolatopsismentioning
confidence: 99%
“…The genomic studies have revealed that Amycolatopsis have comparatively large genomes *5 Mb (A. halophila YIM93223-10) to 10.86 Mb (A. balhimycina FH 1894), circular chromosomes and contains over 20 secondary metabolic gene clusters. As these bacteria are mostly soil dwellers, they experience a diverse and changing habitat which may benefit from a larger repertoire of genes allowing the organism to acclimatize and adapt to the changing conditions [17]. The occurrence of indigenous plasmids in this genus is also not very common.…”
Section: General Features Of the Genus Amycolatopsismentioning
confidence: 99%
“…The genus Amycolatopsis is well known for the commercial production of multiple antibiotics, including the important broad spectrum antibiotics rifamycin and, vancomycin ( Xu et al, 2014 ; Chen et al, 2016 ). These strains also have the potential to produce a number of other secondary metabolites and bioactive molecules ( Adamek et al, 2018 ) and, can be exploited for a range of biotechnological applications ( Davila Costa and Amoroso, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Within the actinomycetes, the genus Streptomyces is the most prolific and most studied producer of secondary metabolites, but members of the families Pseudonocardiaceae and Micromonosporaceae have also shown to produce a broad diversity of bioactive molecules. Among Pseudonocardiaceae , members of the genus Amycolatopsis produce several relevant secondary metabolites, such as balhimycin, vancomycin, avoparcin, ristomycin, chelocardin, chloroeremomycin, ECO-0501 and rifamycin (Chen et al, 2016 ; Kumari et al, 2016 ). More recently, other antibiotics have been described from some Amycolatopsis strains such as macrotermycins A–D (Beemelmanns et al, 2017 ), pargamicins B–D (Hashizume et al, 2017 ) and rifamorpholines A–E (Xiao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%